The impact of customer service on customer loyalty and retention in Zenith Bank Ghana Limited - Nyarko, Mary Ekumah (2017)
A Thesis submitted to the School of Business, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the award of Master of Business Administration in Strategic Management and Consulting